Reconciling material cultures in archaeology with genetic data: the nomenclature of clusters emerging from archaeogenomic analysis - Eisenmann, Stefanie; Maran, Joseph (Scientific reports, 2018)
Genome-wide ancient DNA analysis of skeletons retrieved from archaeological excavations has provided a powerful new tool for the investigation of past populations and migrations. An important objective for the coming years is to properly integrate ancient genomics into archaeological research. This article aims to contribute to developing a better understanding and cooperation between the two disciplines and beyond. It focuses on the question of how best to name clusters encountered when analysing the genetic makeup of past human populations. Recent studies have frequently borrowed archaeological cultural designations to name these genetic groups, while neglecting the historically problematic nature of the concept of cultures in archaeology. After reviewing current practices in naming genetic clusters, we introduce three possible nomenclature systems (‘numeric system’, ‘mixed system (a)’, ‘geographic-temporal system’) along with their advantages and challenges.
Gesehen am 02.04.2020